2015
DOI: 10.1109/taslp.2015.2405482
|View full text |Cite
|
Sign up to set email alerts
|

Keyword Extraction and Clustering for Document Recommendation in Conversations

Abstract: This paper addresses the problem of keyword extraction from conversations, with the goal of using these keywords to retrieve, for each short conversation fragment, a small number of potentially relevant documents, which can be recommended to participants. However, even a short fragment contains a variety of words, which are potentially related to several topics; moreover, using an automatic speech recognition (ASR) system introduces errors among them. Therefore, it is difficult to infer precisely the informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…Many research articles have been found in the literature for keyphrase extraction used machine learning or data mining approaches [23][24][25][26][27][28][29][30][31]. A Naive Bayes approach is used for keyword generation [23].…”
Section: Related Workmentioning
confidence: 99%
“…Many research articles have been found in the literature for keyphrase extraction used machine learning or data mining approaches [23][24][25][26][27][28][29][30][31]. A Naive Bayes approach is used for keyword generation [23].…”
Section: Related Workmentioning
confidence: 99%
“…Firstly, query text should be processed in advance. This procedure results in a keyword set for the query text [11]. The keyword set is the initial expansion set.…”
Section: Semantic Expansionmentioning
confidence: 99%
“…Number of methods has been proposed to automatically extracting keywords from a text, which are also applicable for transcribed conversation. The earliest technique has used word frequencies and TFIDF values to rank words for extraction [1].…”
Section: Related Workmentioning
confidence: 99%